2014
DOI: 10.5935/1678-9741.20140046
|View full text |Cite
|
Sign up to set email alerts
|

Addition of long-distance heart procurement promotes changes in heart transplant recipient waiting list status

Abstract: ObjectiveEvaluate the addition of long-distance heart procurement on a heart transplant program and the status of heart transplant recipients waiting list.MethodsBetween September 2006 and October 2012, 72 patients were listed as heart transplant recipients. Heart transplant was performed in 41 (57%), death on the waiting list occurred in 26 (36%) and heart recovery occurred in 5 (7%). Initially, all transplants were performed with local donors. Long-distance, interstate heart procurement initiated in February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…Similar findings have been corroborated in subsequent studies in which allograft ischemic time has extended beyond 300 minutes without compromising graft function or survival [8][9][10]. More recently, Atik and colleagues [11] demonstrated that the addition of long-distance heart procurements could expand the viable donor pool and reduce wait list mortality without compromising 30-day or 1-year survival. Although previous literature has demonstrated a detrimental effect of longer ischemic times on mortality after heart transplantation, the survival impact of the donor location relative to recipient location has not been previously elucidated.…”
supporting
confidence: 62%
“…Similar findings have been corroborated in subsequent studies in which allograft ischemic time has extended beyond 300 minutes without compromising graft function or survival [8][9][10]. More recently, Atik and colleagues [11] demonstrated that the addition of long-distance heart procurements could expand the viable donor pool and reduce wait list mortality without compromising 30-day or 1-year survival. Although previous literature has demonstrated a detrimental effect of longer ischemic times on mortality after heart transplantation, the survival impact of the donor location relative to recipient location has not been previously elucidated.…”
supporting
confidence: 62%